Perbadingan Estimasi Curah Hujan MRR dan TRMM 3B42 Sebagai Input Model Hidrologi HBV Studi Kasus DAS Bedadung - Muhamad Zulvi Alhamda; Entin Hidayah; Wiwik Yunarni (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2020)
The limitations of spatial and temporal distribution of rain gauge networks causes inaccuracies in prediction of hydrological modeling. The availability of satellite rain data products is a potential to overcome this limitation. This studies objective is to compare the quality of rain data from the recording of the Manual Rainfall Recorder (MRR) with satellite data TRMM 3B42 which is entered in the HBV hydrological modeling. Calibration results shows that HBV modeling performance with MRR rain data input is better than TRMM. R2 and NSE values from MRR rain data input were 0.7153 and 0.7133 respectively with a mean error of 89 (mm / year). While the R2 and NSE values of the TRMM 3B42 satellite rain data input were 0.57 and 0.55 with a mean error of 305 (mm / year), respectively.